Comparing the effectiveness of schema therapy and acceptance and commitment therapy on the tolerance of emotional distress, sexual dysfunction and psychological capital of patients with multiple sclerosis - Nazari, Abbas; Saedi, Sara; Abdi, Mansour (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The present study was conducted with the aim of comparing the effectiveness of schema therapy and acceptance and commitment therapy on the tolerance of emotional distress, sexual dysfunction and psychological capital in patients with multiple sclerosis. Methods: The current research is a semi-experimental type with a pre-test, post-test and follow-up design with two experimental groups and one control group. The statistical population included all the patients with multiple sclerosis in Central Province in the year 2021, and according to the arrangements made with the MS Association of Arak city, their total number is 1200. In this study, statistical samples of 45 people were selected as available and then randomly assigned to 3 groups of 15 people including treatment plan groups (15 people), treatment based on acceptance and commitment (15 people) and control group ( 15 people) were randomly replaced. The research tools included the emotional distress tolerance questionnaire of Simmons and Gaher (2005), the sexual performance questionnaire of Rosen et al. (2000) and the psychological capital questionnaire of Lutans et al. (1999). Schema therapy was based on Yang et al.'s (2003) 12-session protocol, and commitment and acceptance-based therapy was based on Eifert and Forsyth's (2004) eight-session protocol. Finally, analysis of variance of repeated measures using SPSS version 22 software was used to analyze the data. Results: The results showed that there is a significant difference between the effect of schema therapy and therapy based on acceptance and commitment on the tolerance of emotional distress, sexual dysfunction and psychological capital in patients with multiple sclerosis (P=0.01). The effect was reported to be stable during follow-up. Conclusion: Therefore, it can be said that there is a significant difference between the three groups in the post-test scores after adjusting the pre-test scores, and also, the confirmation results showed that schema therapy and t acceptance and commitment therapy t on the tolerance of emotional distress , sexual performance and psychological capital skewness among patients with multiple sclerosis has been stable.